ANALISIS KEANDALAN DELIVERY MAN SEBAGAI UPAYA PENCEGAHAN KECELAKAAN PT. COCA COLA DISTRIBUTION DI SEMARANG - Nurul Ufuk Nuansa; Ekawati Ekawati; Baju Widjasena (Jurnal Kesehatan Masyarakat (Undip), 2016)
Indonesian National Police (INP) recorded 80 per day or 3 people per hour die in road traffic accidents during 2013. Some of the causes of traffic accidents is the use of drugs, use of personal protective equipment compliance is low, the condition of the machine , breaking traffic lights and or other disciplinary action in driving. This study aimed to analyze the reliability of Delivery Man in PT.Coca Cola Distribution Semarang in conducting pre-drive inspection. This research is a quantitative and qualitative descriptive through cross sectional approach using SPAR-H method in calculating the reliability Delivery Man. Sampling techniques saturate some 24 of Delivery Man and seven informants triangulation. The results showed that the reliability Delivery Man without considering the dependence factor is 0.999958367 relatively high reliability with 3 negative PSF are the availability of time, experience / training, and work processes. While reliability Delivery Man by taking into account relatively low dependence upon examination tread components (0), the condition of the fan belt worn / crack (0), tire pressure (0.4999979184), spare tire (0.4999979184), comprehensiveness and firmness tire wheel bolts (0,499995838), the completeness of the jack lock (0,499995838), batteries (0,499995838), radiators (0,499995838), engine oil (0,499995838), brake fluid (0,499995838), horn (0,499995838), belts (0,499995838), safety element (0,499995838) and brakes (0,499995838). While reliability Delivery Man by taking into account a relatively high reliance for electrical inspection large lamps (0,857135721), the turn signal (0,857135721), the brake lights (0,857135721), reverse light (0,857135721), and light box (0,857135721).